2018
DOI: 10.1016/j.comptc.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

DFT investigation of methane metathesis with L2AnCH3 actinide complexes catalysts (L = Cl, Cp, Cp*; An = Ac, Th, Pa, U, Np, Pu)

Abstract: In order to understand the catalytic activity of the actinide complexes L 2 AnCH 3 (An = Ac, Th, Pa, U, Np and Pu; L = Cl, Cp and Cp*) towards the activation of the C-H bond of methane, relativistic ZORA/DFT investigations have been carried out. The results obtained from Linear Transit (LT) and Intrinsic Reaction Coordinate (IRC) calculations show that the mechanism involved in these reactions starts with a proton transfer from methane to the methyl group of the complex leading to the formation of a four cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The U­[5d] valence space of the heavy element includes the 5f/6s/6p/6d/7s/7p shells (14 valence electrons). Several studies have shown that the ZORA/BP86/TZP approach reproduces the experimental geometries and ground-state properties of f-element compounds with a satisfying accuracy. ,, In our case, we carried out first the full geometry optimizations of the species under consideration, in the gas phase, at the spin unrestricted level. Next, the geometries were re-optimized in the THF solvent using the COSMO model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The U­[5d] valence space of the heavy element includes the 5f/6s/6p/6d/7s/7p shells (14 valence electrons). Several studies have shown that the ZORA/BP86/TZP approach reproduces the experimental geometries and ground-state properties of f-element compounds with a satisfying accuracy. ,, In our case, we carried out first the full geometry optimizations of the species under consideration, in the gas phase, at the spin unrestricted level. Next, the geometries were re-optimized in the THF solvent using the COSMO model.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it is likely that the more pronounced covalent character of the actinide−ligand bonds than lanthanide−ligand ones, involving the 5f electrons will play a role on their electrochemical properties. 4,5,17,18,22 In view of the rich diversity of organo−uranium complexes and the importance of the redox chemistry in the reactivity processes, 17,18,27,30,35,61,62 the aim of this work is to investigate the redox properties not only to get access theoretically to the electrochemical potentials but also to corelate these properties to the ligand's nature. The target systems are the series of pentavalent bis(cyclopentadienyl) imido-uranium(V) Cp 2 U( N−Ar)X complexes derived from [(C 5 Me 5 ) 2 U V (N−Ar)(X)] (Ar = 2,6-i Pr 2 -C 6 H 3; X = OTf, SPh, NPh 2 , OPh, Me, Ph, C CPh, NCPh 2 ) complexes (Figure 1), synthetized by the Kiplinger's group, 38,39 for which U V /U IV and U VI /U V redox (E 1/2 ) half-wave potentials have been measured for almost all of them.…”
Section: ■ Introductionmentioning
confidence: 99%